Modern systemic therapy concepts in cervical cancer. Innovations from the S3 guideline: "Diagnosis, treatment and after care of the patient with cervical cancer" - Koch, Martin; Mehlhorn, Grit; Beckmann, Matthias (Onkologe, 2016)
The problems of uncertain treatment, mortality and morbidity rates that have not declined over the last 15 years, and the current wide variations in treatment, made necessary an upgrade from the existing Level 2k consensus-based guideline from 2008 to a Level 3 guideline. These factors also induced the current Level 3 guideline on diagnosis, treatment, and follow-up of patients with cervical carcinoma (AWMF register no. 032-033OL) since 2014. This overview describes the current standard of cervical cancer treatment. Therefore, it focusses on the drug therapy of patients suffering from cervical cancer. This is in line with the focus of the journal. A further topic is the diagnostic chain that is essential for therapeutic decision-making. Based on the recommendations of the S3 guideline, the current algorithms for treating cervical cancer are shown and discussed. Surgical procedures are mainly carried out in the early stages. From stage IIB, a simultaneous cisplatin-containing radiochemotherapy is recommended. The therapy of choice for non-operable local recurrence or metastasic situation consists of palliative chemotherapy regimens. Since 2014 the addition of a targeted therapy with bevacizumab has been integrated to the treatment approach. Therapy for patients with cervical cancer has changed significantly over the last decades. There are various new therapeutic options, which are applied according to tumour stage and on an individual basis. The decision of which therapeutic method has to be applied is based on the interdisciplinary consultation and is individualized. The patient has to be involved in the decision process. Age and life situation have to be considered as well as the stage of the disease, risk factors and the side effects of the different therapies. The aim is to provide the best quality of life and the best outcome.
EVALuna2:32954